Particle beam deflection imaging for simultaneous characterization of aerosol particle size and charge. (January 2023) - Ban, Loren; van Swaaij, Francesca; Fazzolari, Sandro; Signorell, Ruth
Abstract: We present a novel method referred to as Particle Beam Deflection Imaging (PBDI) for the simultaneous characterization of the size and electric charge distribution of submicrometer (currently ∼200–800 nm) aerosol particles in real-time (currently ≤30 s). It combines aerodynamic and electrostatic particle deflection, providing two-dimensional information on size and charge in a single two-dimensional light scattering image. The image allows one to extract information on charge-averaged and charged-resolved particle size distributions, and on size-dependent bipolar charge distributions. The current prototype has a size resolution of <50 nm and can resolve individual charge states. Compared to Scanning Mobility Particles Sizers (SMPS), the PBDI offers the advantage of providing simultaneous size and charge information at higher size resolution in a significantly shorter measurement time, hence allowing real-time characterization of volatile aerosol particles. Highlights: Size and charge of submicrometer aerosol particles are characterized simultaneously. Aerodynamic and electrostatic deflection yield 2-dimensional information. Resolution of <50 nm and sensitivity to individual charge states is demonstrated. The method enables real-time characterization of volatile particles.